Perancangan Sistem Informasi Manajemen pada Gudang di PT. Clandys Cirebon - Jimmy Chang Liong; I Gede Agus Widyadana; Iwan Halim Sahputra (Jurnal Titra, 2022)
In meeting market demands and competition, many companies focus their attention by making various efforts to market their products, gain the largest market share, and increase company profits by improving, improving, or developing the systems they have. Companies with fast distribution, such as the retail business sector, need adequate warehouse facilities so that the needs of consumers or stores can be met optimally. PT. Clandys is a company engaged in the retail of baby and household equipment. The main problems that exist at PT. Clandys are the warehouse system that is still poorly coordinated and the inventory checking that still uses the manual system. With the problems in the PT. Clandys warehouse, a good warehouse system. is needed. The warehouse system that has been created can connect the central warehouse and branch warehouses to each other, provide notifications, as well as automatic matching for goods receipt transactions and stock taking. In addition, a warehouse system was also created to develop other transactions in the PT. Clandys warehouse. Other transactions at PT. Clandys such as mutations, returns, and pre-orders of goods can be coordinated between warehouses and the warehouse system  created.